Understanding Customer Trust and Loyalty: The Impact of Brand Image and Online Reviews on Nivea Sunscreen in Jakarta - Genoveva, Genoveva; Simatupang, Kristina (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
Sun exposure with high ultraviolet radiation is one cause of skin damage human and skin cancer in Indonesia, especially Jakarta. This can be prevented by applying sunscreen with appropriate SPF content. Recently, many sunscreen products have come into the market, which is challenging a long-standing brand such as Nivea, which has been offering sunscreen products in Indonesia for a some time which is indicated by a decline in Nivea's Top Brand Index percentage from 2022 to 2024. This study is to investigate the effects of brand image and online customer reviews on customers' trust, focusing on how the two affect customers' loyalty to Nivea sunscreens in Jakarta. The data presented in this study were collected by applying questionnaires via Google Forms, with a total of 145 respondents. The data analysis technique used SmartPLS 4.0. The results of this study indicate that: brand image has a positive influence on customer trust, online customer reviews have a positive influence on customer trust, and brand image has a positive influence on customer loyalty, Online customer reviews have no positive influence on customer loyalty, customer trust has a positive influence on customer loyalty, customer trust has a significant mediating effect on brand image on customer loyalty. Customer trust has a significant mediating influence on online customer reviews and customer loyalty.